ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT UNTUK MENILAI KINERJA KEUANGAN PT. LION METAL WORKS TBK PERIODE 2020-2023 - Agus Riyanto; Ali Mushofa; Gandi Adnan (University of Widya Gama Mahakam Samarinda, 2025)
This study aims to analyze the financial performance of PT. Lion Metal Works Tbk for the period 2020– 2023 using cash flow ratio analysis. The main issue addressed is the decline in the company’s cash flow, which has impacted its liquidity and financial stability. The research method used is descriptive qualitative, utilizing secondary data from cash flow statements, income statements, and statements of financial position. The analyzed ratios include: operating cash flow to current liabilities (AKO), cash coverage to interest (CKB), operating cash flow to capital expenditure (PM), operating cash flow to total debt (TH), and operating cash flow to net income (AKB). The results show that the AKO, CKB, PM, TH, and AKB ratios tend to fall below 1, indicating poor financial performance. The company experienced liquidity pressures and a reliance on external funding. However, in 2023, there was an increase in cash flow from financing activities, improving the company’s cash position. These findings demonstrate that the cash flow statement is an effective tool for comprehensively evaluating a company’s financial performance.